Competencies, learning outcomes and forms of assessment: the use of Tuning Methodology in Russia - Artur Demchuk; Yevgeniya Karavaeva; Yelena Kovtun; Svetlana Rodionova (Universidad de Deusto, 2015)
The article is focused on the correlation of competencies, learning outcomes and the methods of their assessment in the course of current, interim (end-of-module) and final assessment. It provides a general idea of the background and difficulties associated with the use of competence based learning in the Russian context. We propose an algorithm developed by the experts of Association of Classical Universities of Russia based on the methodology of the Tuning Educational Structures in Europe (TUNING) international project with special emphasis on assessing achievement of learning outcomes. By way of illustration, the undergraduate programmes in Philology and Psychology are discussed.